Calpain-1 is required for hydrogen peroxide-induced myotube atrophy - McClung, J. M. (American Physiological Society, 2009)
Recent reports suggest numerous roles for cysteine proteases in the progression of skeletal muscle atrophy due to disuse or disease. Nonetheless, a specific requirement for these proteases in the progression of skeletal muscle atrophy has not been demonstrated. Therefore, this investigation determined whether calpains or caspase-3 is required for oxidant-induced C2C12 myotube atrophy. We demonstrate that exposure to hydrogen peroxide (25 μM H(2)O(2)) induces myotube oxidative damage and atrophy, with no evidence of cell death. Twenty-four hours of exposure to H(2)O(2) significantly reduced both myotube diameter and the abundance of numerous proteins, including myosin (−81%), α-actinin (−40%), desmin (−79%), talin (−37%), and troponin I (−80%). Myotube atrophy was also characterized by increased cleavage of the cysteine protease substrate αII-spectrin following 4 h and 24 h of H(2)O(2) treatment. This degradation was blocked by administration of the protease inhibitor leupeptin (10 μM). Using small interfering RNA transfection of mature myotubes against the specific proteases calpain-1, calpain-2, and caspase-3, we demonstrated that calpain-1 is required for H(2)O(2)-induced myotube atrophy. Collectively, our data provide the first evidence for an absolute requirement for calpain-1 in the development of skeletal muscle myotube atrophy in response to oxidant-induced cellular stress.